(untitled) (Weinheim, 2010)
Closing a gap in the literature, this is the first comprehensive handbook on this modern and important polymer topic. Edited by highly experienced and top scientists in the field, this ready reference covers all aspects, including material science, biopolymers, gels, phase separating systems, frontal polymerization and much more. The introductory chapter offers the perfect starting point for the non-expert.
Keywords: Polymers,Động học phân tử,Polyme,Molecular dynamics